PEMBERDAYAAN LITERASI KEUANGAN UMKM MELALUI KLINIK WIRAUSAHA KELUARGA AISYIAH KLATEN - Nugroho, Arif Julianto Sri; Darmo, M. Pujo; Santoso, Gunawan Budi; Widayanti, Sukasih Ratna (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2022)
Pemberdayaan UMKM Keluarga Aisyiyah in the community is very important. Keluarga Aisyiyah plays a role in empowering families in improving the welfare and family quality in aspects of health, morals, faith and behavior. This is inline with one of the main programs of UMKM Keluarga Aisyiyah namely education and skills. On this occasion, as a form of community services, the authors cooperate with UMKM keluarga Aisyiyah in order to improve family welfare in the local environment through the improvement of cooking , handircaft skills that are expected to be useful later.